Accessing depth-resolved high spatial frequency content from the optical coherence tomography signal - Sergey Alexandrov (Nature Portfolio, 2021)
Abstract Optical coherence tomography (OCT) is a rapidly evolving technology with a broad range of applications, including biomedical imaging and diagnosis. Conventional intensity-based OCT provides depth-resolved imaging with a typical resolution and sensitivity to structural alterations of about 5–10 microns. It would be desirable for functional biological imaging to detect smaller features in tissues due to the nature of pathological processes. In this article, we perform the analysis of the spatial frequency content of the OCT signal based on scattering theory. We demonstrate that the OCT signal, even at limited spectral bandwidth, contains information about high spatial frequencies present in the object which relates to the small, sub-wavelength size structures. Experimental single frame imaging of phantoms with well-known sub-micron internal structures confirms the theory. Examples of visualization of the nanoscale structural changes within mesenchymal stem cells (MSC), which are invisible using conventional OCT, are also shown. Presented results provide a theoretical and experimental basis for the extraction of high spatial frequency information to substantially improve the sensitivity of OCT to structural alterations at clinically relevant depths.